The EMECAM project: a multicentre study on air pollution and mortality in Spain: combined results for particulates and for sulfur dioxide. Issue 5 (1st May 2002) - Ballester, F; Sáez, M; Pérez-Hoyos, S; Iñíguez, C; Gandarillas, A; Tobías, A; Bellido, J; Taracido, M; Arribas, F; Daponte, A; Alonso, E; Cañada, A; et al.
Abstract : Objective: The EMECAM study is a collaborative effort to evaluate the impact of air pollution on mortality in Spain. In this paper the combined results are presented for the short term effects of particulates and sulfur dioxide on both daily mortality for all and for specific causes. Methods: The relation between daily mortality for all causes, cardiovascular diseases, and respiratory diseases, and air pollution for particulates (daily concentrations) and SO2 (24 and 1 hour concentrations) was assessed in 13 Spanish cities for the period 1990–6. With a standardised method, magnitude of association in each city was estimated by Poisson regression in a generalised additive model. Local estimates were obtained from both single and two pollutant analyses. Lastly, combined estimates for each cause and pollutant were obtained. Results: For combined results, in single pollutant models a 10 μg/m 3 increase in the concentration of the mean of the concurrent and one day lag for black smoke was associated with a 0.8% (95% confidence interval (95% CI) 0.4 to 1.1%) increase in total mortality. The estimates for total suspended particles (TSPs) and particulate matter of aerodynamic diameter <10 μm (PM10 ) and total mortality were slightly lower. The same increase in concentrations of SO2 was associated with a 0.5% increase in daily deaths. For groups of specific causes, higher estimations were found, specially for respiratory conditions. Peak concentrations of SO2 showed significant associations with the three groups of mortality. When two pollutant analyses were performed, estimates for particulates, specially for black smoke, did not substantially change. The estimates for daily concentrations of SO2 were greatly reduced, but, on the contrary, the association with peak concentrations of SO2 did not show any change. Conclusions: There is an association between mortality and pollution through particulates among city populations in Spain. Peak rather than daily concentrations of SO2 were related to mortality. Results suggest that populations in Spanish cities are exposed to health risks derived from air pollution.